The law and practice of solidarity in the Common European Asylum System: Article 80 TFEU and its added value - Karageorgiou, Eleni (European Policy Analysis, 2016)
Given the current scale of global displacement, in particular from Syria, and the rising death toll of individuals crossing the Mediterranean, the European Union has emphatically stressed the need to work on an effective asylum and immigration policy, through more robust forms of cooperation between Member States. Following the Agenda on Migration in May 2015, a set of new measures and proposals to reform the existing framework on asylum have been launched, including, inter-alia, an emergency relocation mechanism, a proposal to reform the Dublin Regulation, and the development of the EU-Turkey partnership. Their main objective is “to ensure an efficient response to the increased arrivals of refugees and migrants in the EU” and “a high degree of solidarity between the Member States” along the lines of Article 80 TFEU. This begs the question of what solidarity, as the guiding principle of European immigration and asylum policies, entails in terms of states’ obligations and to what extent these obligations have been enforced in view of the current critical situation in Europe. The present paper explores the meaning and functions of the principle of solidarity enshrined in Article 80 TFEU based on the ways in which it has been operationalized through these measures.
Keywords: EU law; migration law; EU-rätt; migrationsrätt